(untitled) (Journal of Bangladesh Academy of Sciences, 2012)
Electrical properties such as electrical resistivity, Hall coefficient, Hall mobility, carrier concentration of p-type GaAs samples were studied at room temperature (300 K). Resistivity was found to be of the order of 5.6 × 10-3?-cm. The Hall coefficient (RH) was calculated to be 7.69 × 10-1cm3/C and Hall mobility (?H) was found to be 131cm2/V-s at room temperature from Hall effect measurements. Carrier concentration was estimated to be 8.12 × 1018/cm3 and the Fermi level was calculated directly from carrier density data which was 0.33 eV. Photoconductivity measurements were carried on by varying sample current, light intensity and temperature at constant chopping frequency 45.60 Hz in all the cases mentioned above. It was observed that within the range of sample current 0.1 - 0.25mA photoconductivity remains almost constant at room temperature 300K and it was found to be varying non-linearly with light intensity within the range 37 - 12780 lux. Photoconductivity was observed to be increasing linearly with temperature between 308 and 428 K. Absorption coefficient (?) of the samples has been studied with variation of wavelength (300 - 2500 nm). The value of optical band gap energy was calculated between 1.34 and 1.41eV for the material from the graph of (?h?)2 plotted against photon energy. The value of lattice parameter (a) was found to be 5.651 by implying X-ray diffraction method (XRD). DOI: http://dx.doi.org/10.3329/jbas.v36i1.10926 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 1, 97-107, 2012